Analysis of modular air distribution and dust control method and its gas discharge law in high-gas coal mine - Haiming YU; Yuxi YE; Weimin CHENG; Xianhang YANG; Sen XIE; Yu CHENG; Hui DONG (Meitan xuebao)
With the continuous improvement of coal mine mechanization, the problem of dust pollution has become increasingly severe, posing a serious threat to the occupational health of miners and mine safety production. Therefore, this study proposes a modular and lightweight wind curtain generator, which forms a modular air separation system and dust control technology for the comprehensive excavation face. Theoretical analysis, numerical simulation, and on-site experiments are combined to simulate the coupling diffusion law of airflow, dust, and gas in the comprehensive excavation face. The influence of the distance between the axial air outlet and the front end on the diffusion of dust and gas is obtained. The simulation results show that different air outlet distances have a significant impact on the airflow field structure and dust diffusion results. When the distance is less than 12 m, the airflow does not form a spiral and flows directly towards the head, resulting in weak dust control effect and high dust concentration in the respiratory tract height; At a distance of 12-18 m, a spiral airflow gradually forms in the tunnel, and a dust control wind curtain pointing forward is formed at a distance of 5-8 m from the front. The dust concentration at the respiratory height is lower than 20 mg/m3 in the area 6 m behind the front. At this time, there is a phenomenon of “dust leakage” in the middle of the tunnel, and the diffusion distance of dust with a concentration close to 0 mg/m3 increases. The gas concentration in the roadway remains within a safe level under different air outlet distances, but when the distances are 7 m and 15 m, the gas concentration in some areas of the roadway increases to over 0.81%. After on-site verification, the relative error of the simulation results was the highest at 11.09%. Through similar simulation experiments, it was found that the application of modular air separation technology significantly reduced the dust diffusion distance, and the high concentration dust area was controlled within a range of 6.24 m from the front end. Compared with the simulation results, the relative error was less than 7.37%, providing new theoretical methods and technical support for the comprehensive excavation of flour dust and gas prevention and control work in high gas environments.